Three phase four wire shunt active power filter from theory to industrial facility tests - Exposto, Bruno Fernandes (2011)
Non-linear loads are very common in present industrial facilities, office buildings and even in our homes. This loads present several Power Quality problems to the electrical grid. The conventional solutions do not solve these problems in a suitable way. Therefore, it is necessary to find new solutions such as Active Power Filters. This paper presents and discusses the main steps that are necessary to implement a Three Phase Four Wire Shunt Active Power Filter from theory to field tests. Therefore it is a contribution on several topics. Starting with the main control theories used on this topology, it explains the p-q Theory in a more detailed way. It also gives a brief presentation of some modulation techniques. There are presented computational simulation results and field tests results of the developed filter operating in an industrial facility.